Attitude of inmates towards the prison library: a predictor of psychological wellbeing - Emasealu, Helen Uzoezi (Faculdade de Filosofia e Ciências, 2019)
Information has been a veritable mechanism in the constant search for knowledge so as to attain developmental objectives. In the same vein, information is vital in the life of all individuals towards the realization of socio-political, economic, and developmental goals, it also serves just the same importance for the survival of incarcerated persons. Adopting correlational study method, this study seeks to define the attitude of inmates toward the prison library and its effect on their psychological wellbeing. Two prisons - Port Harcourt Maximum Prison, Rivers State and Oko Prison, Benin City, Edo State, both in Nigeria, were selected for the study. From the population of convicted inmates in both prisons, 440 males and females were randomly sampled to generate data.A structured questionnaire divided into two sections - attitude scale and psychological wellbeing scale, was used in data collection. Out of the 440 sampled inmates, 393 responded correctly to the questionnaire resulting to 89% response rate. Data was collated and analyzed using descriptive analysis of mean and standard deviation, and linear regression. The results indicated that inmates in both prisons have a positive attitude towards the prison library, and they are also psychologically adjusted in prison. The result also reveals that there is a high positive relationship between inmates' attitude towards the prison library and its psychological wellbeing (r = .540).The study concludes that bibliotherapy can further enhance the effectiveness of other reformation and rehabilitative programs for inmates, and therefore, recommends that the penal system should embrace bibliotherapy as a rehabilitation program for the reformation and rehabilitation of societal offenders.